Climate Change in Robinson’s Narrative (Venice Drowned) - Al Qudah, Omar Ayed Shaman; Al Ahmad, Mohamad Hilmi (Dirasat: Human and Social Sciences, 2024)
Objectives: The current study aims to explore how climate change and global warming are represented in “Venice Drowned” by Kim Stanley Robinson. Additionally, it aims to analyze the strenuous relationship between humans and nature as depicted in this story. Methods: In order to achieve the objectives of this study, both analytical and descriptive techniques were employed. The study provided a detailed summary of the climatic narrative that constitutes the center of this research. Furthermore, the study applied the theory of Ecocriticism to examine how climate change issues are portrayed in this fictional work. Results: The study reveals that climate change in this work occurs naturally, and man had no role to play in that change. The narrative portrays a strained, complex, and multifaceted relationship between humans and nature, highlighting the environmental impact of human actions and the challenges faced by both. Additionally, the study demonstrates the adverse economic, health, and social effects of climate change and global warming on human life. Conclusions: Finally, the study proposes several recommendations, including the need to clarify the means of regulating the relationship between humans and nature, explain the roles of natural and human causes of climate change, and recognize the contribution of science fiction in raising awareness about climate change and global warming.